2022
DOI: 10.1155/2022/2076021
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Lactic Acid Bacteria from Fermented Milk Produced in Jimma Town, Southwest Ethiopia, and Evaluation of their Antimicrobial Activity against Selected Pathogenic Bacteria

Abstract: Background. Raw milk is usually contaminated with pathogenic bacteria. Fermentation of milk is important to inhibit the growth of contaminants, spoilage, and pathogenic bacteria. The objective of this study was to isolate lactic acid bacteria from fermented milk and evaluate their antimicrobial activity against selected pathogenic bacteria. Methods. Laboratory-based experimental study design was conducted from May-July, 2021.Three samples of Ergo (each of 250 ml) were collected from Jimma town. Lactic acid bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…These variations can be attributed to differences in their physiological effectiveness and disparities in gene composition, affecting enzyme activity and metabolic efficiency. 8,21 Moreover, we identified the most potent bacteriocin from a Lactobacillus strain isolated from camel's milk as L. acidophilus, this result was in line with Ahmed and Kanwal (2004) study, which demonstrated its effectiveness in converting lactose sugar into lactic acid. 22 Similar results were reported by Pyar and Peh in 2014 23 and Mithun, Dipak, and Sheela in 2015.…”
Section: Discussionsupporting
confidence: 86%
“…These variations can be attributed to differences in their physiological effectiveness and disparities in gene composition, affecting enzyme activity and metabolic efficiency. 8,21 Moreover, we identified the most potent bacteriocin from a Lactobacillus strain isolated from camel's milk as L. acidophilus, this result was in line with Ahmed and Kanwal (2004) study, which demonstrated its effectiveness in converting lactose sugar into lactic acid. 22 Similar results were reported by Pyar and Peh in 2014 23 and Mithun, Dipak, and Sheela in 2015.…”
Section: Discussionsupporting
confidence: 86%
“…De Man-Rogosa-Sharpe (HiMedia, India) agar that contains 1% CaCO 3 (MRSA) was prepared to isolate LAB from the food samples. Bacterial isolation was carried out using the serial dilution method [24][25][26][27]. One gram of each food sample was transferred into 9 mL of physiological saline solution (0.9% NaCl) to obtain the first dilution (10 -1 ).…”
Section: Isolation and Screening Of Lactic Acid Bacteria (Lab)mentioning
confidence: 99%
“…For phenotypic characterisation, these isolates were subjected to Gram staining, catalase test, salt tolerance test, Simmon citrate test, temperature endurance test, and Triple Sugar Iron (TSI) test [9]. For the catalase test, a drop 30%(v/v) hydrogen peroxide was added to cell sample smeared onto a glass slide.…”
Section: Phenotypic Characterisationmentioning
confidence: 99%